Spiroguanidine rhodamines as fluorogenic probes for lysophosphatidic acid. Issue 9 (17th December 2014) - Wang, Lei; Sibrian-Vazquez, Martha; Escobedo, Jorge O.; Wang, Jialu; Moore, Richard G.; Strongin, Robert M.
Abstract : Fluorescent indicators have been developed that enable the determination of lysophosphatidic acids via signaling that is independent of the size or degree of unsaturation of the fatty acid side chain. Abstract : Direct determination of total lysophosphatidic acid (LPA) was accomplished using newly developed spiroguanidines derived from rhodamine B as universal fluorogenic probes. Optimum conditions for the quantitative analysis of total LPA were investigated. The linear range for the determination of total LPA is up to 5 μM with a limit of detection of 0.512 μM.